“Hard work paid off” - Norhidayah, Mohamad (2018)
Kuantan, 28 February - Universiti Malaysia Pahang (UMP) was ranked five-star in Malaysia Research Assessment (MyRA) for the achievement in research, development and commercialization programme implemented by the university throughout 2016 based on the results announced by the Ministry of Education Malaysia (MoHE) today.